Чорноморське козацьке військо в межиріччі Південного Бугу та Дністра: історіографія питання - Ложешник, О. (Чорноморська минувшина, 2020)
У статті проаналізовано історіографію Чорноморського війська під час його перебування в Буго-Дністровському межиріччі. Головний наголос зроблено на висвітленні проблеми оселення та господарського освоєння краю. Виокремлено та синтезовано етапи розвитку, важливі напрямки історичних досліджень та їхні особливості, висвітлено стан сучасних історичних пошуків та вказано на їхні перспективи. The article analyzes the historiography of the Black Sea troops during their stay in the Bug- Dniester interfluves, which objectively can be divided into three main periods, each of which is characterized by its own "vision" and interpretation of the history of the Black Sea troops. So, for example, if the first period is characterized by an ambiguous attitude to the Ukrainian Cossacks: the idealization changes to openly biased approaches, which completely deny any constructivism in their history; the third period is characterized by a burst of interest in the history of the Black Sea troops on the interfluve territory, the identification of new archival documents and rethinking of previously known facts. The diversity of research allows, by comparing information and comparing facts in the works of different authors, to objectively cover the history of the army during its stay in the Bugo-Dniester interfluves area. By the beginning of the 20th century a certain tradition in the study of the history of the Black Sea troops was formed. Its main features were: the use of a narrow range of sources of official origin, absolutization of the role of the Russian Empire government in the history of the Black Sea troops. This is explained by the fact that a critical analysis of the government policy and activities of the local administration on the Cossacks was not possible for a number of objective reasons: the stay of this topic in the shadow of more topical historiographical problems, limited access to the source base. After 1917 studies of the history of the Black Sea Cossacks were transferred to the level of local history studies and for ideological reasons almost never took place. The next stage in the studying of the history of the army is connected with the second half of the 20th century. Among the most striking works of this period are the studies of V. Golobutsky and A. Bachinsky. Thanks to the use of archival materials, a significant part of which was first introduced into the scientific turnover A. Bachinsky enriched the factual basis of the history of the Black Sea Army Cossacks at that time, drawing attention to their relations with the Turkish Cossacks. Thus, during the second half of the twentieth century, the scope of research on the history of the Black Sea Army during its settlement in the Bugo-Dniester interfluvial was significantly expanded, new sources were used to study the socio-economic aspects of the Cossacks' situation during that period. So, investigating the stay of the Cossacks of the Black Sea troops on the territory of Bug-Dniester interfluves, historians passed a way from the scientific interest in the history of the south of Ukraine as a whole (in the first half of the XIX century) to the fundamental works on various aspects of social and economic history of irregular Cossack formation of the late XVIII century (at the end of the ХХ – at the beginning of the XXI century).